Bacterial flora in the conjunctiva among the patients undergoing cataract surgery - Satish, K.; Chandra, T. Jaya (International Journal of Research in Medical Sciences, 2019)
Background: The present study was aimed in identifying the normal organisms found in the conjunctiva of healthy eyes among the individuals undergoing cataract surgery and also antibacterial susceptibility of the isolates. Cataract is the major cause of blindness in the developing countries, cataract surgery is one of the common surgical practices. Methods: Study was conducted in the department of Microbiology, GSL Medical College from May to July 2018. Surgically removed cataract lens was collected in sterile nutrient broth and transported to Microbiology laboratory for culture and sensitivity testing. The broths were incubated at 37ºC for 24 hours subcultured on Blood agar, MacConkey agar and Nutrient agar, incubated aerobically at 37ºC for 24 hours and then examined for bacteria growth according to standard protocol. After incubation growth was identified by colony morphology, gram staining and biochemical tests. Antibiotic sensitivity testing was done on Muller-Hinton agar by the disk diffusion method. Results: During the study period, 58 samples were collected; the male female ratio was 1.14. Maximum strains were isolated among female; the male female ration was 0.95. Increase in flora was observed with age. No significant drug resistance was observed. Conclusions: This is a hospital based study which is not true representation of the community. Hence a community based study with large sample by considering the comorbid conditions such as occupation, diabetes, immune status can give the authentic data on the conjunctival flora.